2015
DOI: 10.1038/srep17231
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diversity is strongly associated with historical penguin activity in an Antarctic lake sediment profile

Abstract: Current penguin activity in Antarctica affects the geochemistry of sediments and their microbial communities; the effects of historical penguin activity are less well understood. Here, bacterial diversity in ornithogenic sediment was investigated using high-throughput pyrosequencing. The relative abundances of dominant phyla were controlled by the amount of historical penguin guano deposition. Significant positive correlations were found between both the bacterial richness and diversity, and the relative pengu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 69 publications
1
15
0
2
Order By: Relevance
“…In addition, although the data comparison was not between samples obtained from the same bird, the composition similarity shown between the compared cloacae/faeces and stomachs suggests that there could possibly be a microbial link between the stomachs, cloacae and faeces. Previously, Ma et al (2013) and Zhu et al (2015) reported that penguin deposited materials may change the geochemical component in Antarctic soils for microbial succession. The information obtained here is therefore useful for further study to understand the transfer and establishment of microbes from penguin internal guts to deposited materials and subsequently input to the surrounding soil microbial ecosystem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, although the data comparison was not between samples obtained from the same bird, the composition similarity shown between the compared cloacae/faeces and stomachs suggests that there could possibly be a microbial link between the stomachs, cloacae and faeces. Previously, Ma et al (2013) and Zhu et al (2015) reported that penguin deposited materials may change the geochemical component in Antarctic soils for microbial succession. The information obtained here is therefore useful for further study to understand the transfer and establishment of microbes from penguin internal guts to deposited materials and subsequently input to the surrounding soil microbial ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…prey-associated and marine bacteria) in the stomachs might have an immediate impact on the chicks relying on regurgitate for food. Furthermore, as penguins feed in the sea and breed on the land, besides their deposited materials being the key contributors of nutrients to the typically nutrient-poor Antarctic soils and subsequently for the microbial succession in the regional terrestrial ecosystem (Ugolini 1972;Heine and Speir 1989;Sun et al 2000Sun et al , 2004Ma et al 2013;Zhu et al 2015), their stomach microbes could possibly also be input to the surrounding soil microbial ecosystem through regurgitation or defecation. In order to examine how the stomach microbiota influences both penguins, chicks and the surrounding terrestrial ecosystem, it is important first to understand which microbes are present in penguin stomachs, and the factors that shape these communities.…”
Section: Introductionmentioning
confidence: 99%
“…Although in some cases seabird colonies have profoundly altered the biogeochemical processes that occur in coastal surface systems (soils, sediments, and waters), and have transformed plant communities (for example, Mediterranean and Atlantic islands 6 , 9 , North-East Scottish coast 11 , and Pacific reef corals 13 ), most studies revealing biogeochemical and ecological alterations have been mostly of local interest and importance to particular areas 6 , 9 14 (Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that sea animals significantly increased tundra N 2 O emissions in coastal Antarctica ( Zhu et al, 2011 , 2013 , 2015b ; Bao et al, 2018 ). Furthermore, penguin and seal colonies have a significant impact on tundra soil bacterial community structure ( Ma et al, 2013 ; Zhu et al, 2015a ), and the abundances, community compositions, and activities of ammonia oxidation archaea (AOA) and bacteria (AOB) are closely related to sea animal activities ( Wang Q. et al, 2019 ). Every summer, a large number of penguin and seal breed on the ice-free land along the coasts of Antarctica and surrounding islands.…”
Section: Introductionmentioning
confidence: 99%